2013
DOI: 10.5336/medsci.2012-32626
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Hydrogen Gas Therapy for Prevention of Renal Ischemia/Reperfusion Injury in Rat Model

Abstract: schemia/reperfusion (I/R) injury, including arterial occlusion, shock, and organ transplantation, is a common finding in clinical settings. I/R of native and transplant kidneys is a major cause of acute kidney injury Turkiye Klinikleri J Med Sci 2013;33(4) 1097 Inhaled Hydrogen Gas Therapy for Prevention of Renal Ischemia/Reperfusion Injury in Rat Model A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : We aimed to show the short-and long-term protective effects of inhaled hydrogen gas on renal ischemia/r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In this model, 30 rats were used, and 2% hydrogen gas was given to the study group during ischemia before and for one hour after ischemia. The investigators reported that hydrogen gas significantly reduced IR damage in the kidney in the early and late periods in the histopathological examination of nephrectomy material performed after six hours (early stage) and 14 days (late period) of ischemia [ 16 ]. The nephroprotective effect of remifentanil and dexmedetomidine was investigated in the IR model created in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, 30 rats were used, and 2% hydrogen gas was given to the study group during ischemia before and for one hour after ischemia. The investigators reported that hydrogen gas significantly reduced IR damage in the kidney in the early and late periods in the histopathological examination of nephrectomy material performed after six hours (early stage) and 14 days (late period) of ischemia [ 16 ]. The nephroprotective effect of remifentanil and dexmedetomidine was investigated in the IR model created in the kidney.…”
Section: Discussionmentioning
confidence: 99%